The complementary relationship between the Internet and traditional mass media: the case of online news and information - An Nguyen; Mark Western (Information Research: An International Electronic Journal)
Background. The question whether old media are driven out of existence by new media has been a long concern in academic and industrial research but has received no definitive answer. Aim.This paper goes beyond most previous studies of Internet impact on traditional media, which have placed their relationship within a competition-based framework, to specifically investigate the complementary effect of online news and information usage on traditional sources. Method. Secondary data analysis of a national survey of 4270 Australians conducted in late 2003, employing hypothesis testing for the mean, partial correlations, and a linear regression analysis. Results. Online news and information usage at different usage levels is positively associated with the use of traditional news and information sources, especially those that are more information-intensive. Those who relied on the Internet the most for news and information still used traditional sources substantially. Conclusion. The findings suggest that even if a displacement effect takes place, there will be no replacement (absolute displacement): traditional media will still exist to complement the Internet in serving human beings' news and information needs.